CCN family member 2/connective tissue growth factor (CCN2/CTGF) has anti-aging effects that protect articular cartilage from age-related degenerative changes. - Shinsuke Itoh (Public Library of Science (PLoS), 2013)
To examine the role of connective tissue growth factor CCN2/CTGF (CCN2) in the maintenance of the articular cartilaginous phenotype, we analyzed knee joints from aging transgenic mice (TG) overexpressing CCN2 driven by the Col2a1 promoter. Knee joints from 3-, 14-, 40-, and 60-day-old and 5-, 12-, 18-, 21-, and 24-month-old littermates were analyzed. Ccn2-LacZ transgene expression in articular cartilage was followed by X-gal staining until 5 months of age. Overexpression of CCN2 protein was confirmed through all ages in TG articular cartilage and in growth plates. Radiographic analysis of knee joints showed a narrowing joint space and other features of osteoarthritis in 50% of WT, but not in any of the TG mice. Transgenic articular cartilage showed enhanced toluidine blue and safranin-O staining as well as chondrocyte proliferation but reduced staining for type X and I collagen and MMP-13 as compared with those parameters for WT cartilage. Staining for aggrecan neoepitope, a marker of aggrecan degradation in WT articular cartilage, increased at 5 and 12 months, but disappeared at 24 months due to loss of cartilage; whereas it was reduced in TG articular cartilage after 12 months. Expression of cartilage genes and MMPs under cyclic tension stress (CTS) was measured by using primary cultures of chondrocytes obtained from wild-type (WT) rib cartilage and TG or WT epiphyseal cartilage. CTS applied to primary cultures of mock-transfected rib chondrocytes from WT cartilage and WT epiphyseal cartilage induced expression of Col1a1, ColXa1, Mmp-13, and Mmp-9 mRNAs; however, their levels were not affected in CCN2-overexpressing chondrocytes and TG epiphyseal cartilage. In conclusion, cartilage-specific overexpression of CCN2 during the developmental and growth periods reduced age-related changes in articular cartilage. Thus CCN2 may play a role as an anti-aging factor by stabilizing articular cartilage.